Literature and social media - Thomas, Bronwen (London: Routledge, 2020)
'Reading social media both in relation to literature, but also as a literary form in its own right, this lively guide demonstrates that social media platforms have produced their own unique and distinctive forms of creative expression. Bronwyn Thomas takes a unique approach examining how authors interact with readers, but also how social media is used to create an ongoing collaborative discourse. This 360 degree approach to the study of contemporary literary practices, cultures and communities will provide a timely account of the state of art, while also exploring the implications for traditional literary forms and practices and interrogating the rhetoric that so often accompanies discussion of the'new' in this context'--
From the Holodeck to the Tweetdeck: electronic literature, interactivity and participation -- Old Wines in New Bottles? Retelling and reimagining the literary with social media -- The Twittersphere as Literary Playground -- Canons and Curators -- Literary Networks -- New Literary Cultures and Markets -- Afterword.
Includes bibliographical references pages:130-146 and index.
Keywords: Hypertext literature -- History and criticism; Literature and technology; Literature and the Internet; Books and reading -- Technological innovations; Online authorship